2018
DOI: 10.1039/c7ee03195e
|View full text |Cite
|
Sign up to set email alerts
|

Lithium manganese oxyfluoride as a new cathode material exhibiting oxygen redox

Abstract: A new high performance cathode material for Li-ion batteries with a disordered rocksalt structure powered by manganese and oxygen redox.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
280
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(292 citation statements)
references
References 42 publications
11
280
0
1
Order By: Relevance
“…Very recently, a manganese system, Li 2 MnO 2 F, has been already reported. The sample delivers a reversible capacity of nearly 300 mA h g −1 , which partly originates from the anionic redox reaction . In addition, it has been reported that Li 2 Mn 2/3 Nb 1/3 O 2 F also delivers a reversible capacity of approximately 300 mA h g −1 in lithium cells on the basis of Mn 2+ /Mn 4+ redox coupled with partial anionic redox …”
Section: Lithium‐excess Metal Oxyfluorides; Lif‐limo2 Systemmentioning
confidence: 96%
“…Very recently, a manganese system, Li 2 MnO 2 F, has been already reported. The sample delivers a reversible capacity of nearly 300 mA h g −1 , which partly originates from the anionic redox reaction . In addition, it has been reported that Li 2 Mn 2/3 Nb 1/3 O 2 F also delivers a reversible capacity of approximately 300 mA h g −1 in lithium cells on the basis of Mn 2+ /Mn 4+ redox coupled with partial anionic redox …”
Section: Lithium‐excess Metal Oxyfluorides; Lif‐limo2 Systemmentioning
confidence: 96%
“…[195,196] Another way to mitigate Ol oss is the substitution of F À for O 2À . [197,198] Unlike the well-ordered rock-salt structure,bulk fluorination is possible in the disordered rock-salt structure due to local Li-rich environment. [199] F À doping lowers the average anionic valence thereby the composition can accommodate larger amounts of cationic redox so that the excessive anionic redox could be reduced.…”
Section: Stabilizing the Anionic Redoxmentioning
confidence: 99%
“…Fe-Nb-and Fe-Ti-based DRXs have been reported, but in general show lower discharge energy densities compared with Mn redox systems. [24] The recently reported Li 2 Mn 2/3 Nb 1/3 O 2 F/ Li 2 Mn 1/2 Ti 1/2 O 2 F [5] and Li 1.2 Mn 0.2 V 0.6 O 2 [10] compounds prepared by mechanochemical synthesis rely mainly on Mn 2+ / Mn 4+ redox (for Li 1.2 Mn 0.2 V 0.6 O 2 , V 4+ /V 5+ redox as well) to achieve high capacities over 300 mAh g −1 (room temperature, 20 mA g −1 ). Li 1.3 Mn 0.4 Nb 0.3 O 2 prepared using a traditional solid-state synthesis method exhibits a large initial capacity of >290 mAh g −1 (60 °C, 10 mA g −1 ) based partially on Mn 3+ /Mn 4+ redox in addition to a large amount of oxygen redox, but suffers from substantial capacity fading upon extended cycling.…”
mentioning
confidence: 99%